Correlation of the structural and functional domains in the membrane protein Vpu from HIV-1 - Marassi, F. M. (The National Academy of Sciences, 1999)
Vpu is an 81-residue membrane protein encoded by the HIV-1 genome. NMR experiments show that the protein folds into two distinct domains, a transmembrane hydrophobic helix and a cytoplasmic domain with two in-plane amphipathic α-helices separated by a linker region. Resonances in one-dimensional solid-state NMR spectra of uniformly (15)N labeled Vpu are clearly segregated into two bands at chemical shift frequencies associated with NH bonds in a transmembrane α-helix, perpendicular to the membrane surface, and with NH bonds in the cytoplasmic helices parallel to the membrane surface. Solid-state NMR spectra of truncated Vpu(2–51) (residues 2–51), which contains the transmembrane α-helix and the first amphipathic helix of the cytoplasmic domain, and of a construct Vpu(28–81) (residues 28–81), which contains only the cytoplasmic domain, support this structural model of Vpu in the membrane. Full-length Vpu (residues 2–81) forms discrete ion-conducting channels of heterogeneous conductance in lipid bilayers. The most frequent conductances were 22 ± 3 pS and 12 ± 3 pS in 0.5 M KCl and 29 ± 3 pS and 12 ± 3 pS in 0.5 M NaCl. In agreement with the structural model, truncated Vpu(2–51), which has the transmembrane helix, forms discrete channels in lipid bilayers, whereas the cytoplasmic domain Vpu(28–81), which lacks the transmembrane helix, does not. This finding shows that the channel activity is associated with the transmembrane helical domain. The pattern of channel activity is characteristic of the self-assembly of conductive oligomers in the membrane and is compatible with the structural and functional findings.